EXPLORING THE ROLE OF BRAND AWARENESS IN BUILDING CONSUMER TRUST IN ONLINE-BASED MSMEs - Sutopo Sutopo; Sudianto; Abdul Hamid (Journal of Management and Innovation Entrepreneurship (JMIE), 2026)
The growth of online-based MSMEs in Indonesia is strengthening along with the increasing adoption of digital technology and the shift in consumer behavior to the online space. In the context of intense competition and high uncertainty of online transactions, brand awareness is a key element in building consumer trust. This study aims to explore the role of brand awareness in building consumer trust in online-based MSMEs through a literature review (library research). Data were collected from scientific journal articles and relevant books accessed online through Google Scholar and various other credible literature sources. The results of the study indicate that brand awareness not only functions as brand recognition but also serves as a gateway for the formation of consumer perceptions of quality, credibility, and a sense of security. Brand awareness contributes to various trust indicators, such as product reliability, brand integrity, transaction security, competence, performance consistency, goodwill, information transparency, reputation, after-sales service, and the quality of brand communication. In the online MSME ecosystem, digital marketing, social media, and marketplaces serve as strategic channels for building awareness and trust simultaneously. This study develops a conceptual model that positions brand awareness as an initial variable that influences the formation of consumer trust through factors such as product quality, reputation, consumer experience, and digital marketing effectiveness. These findings provide implications for online MSMEs to prioritize strengthening brand awareness as a fundamental strategy for building and maintaining consumer trust in a highly competitive digital environment.